Dynamics of the bird communities in two fragments of Atlantic Forest in Sao Paulo, Brazil - Vianna, Renata M. [UNESP]; Donatelli, Reginaldo J. [UNESP]; Whitacker, Raphael [UNESP]; Martins, Rafael M. [UNESP]; Sementili-Cardoso, Guilherme [UNESP] (Walter De Gruyter Gmbh, 2017)
Birds can be used as bioindicators to evaluate the quality of a habitat. The objective of this study was to record richness and abundance of bird communities in two semi-deciduous forest fragments in Brazil (Olavo Egydio Setubal - OES; and Igure - IGR). A subsequent analysis and comparison of the avifauna structure in each of the fragments were made including previous studies in the same areas. Point counts methodology was chosen for each fragment along 12 months. The results showed the occurrence of a total of 129 bird species for both areas. Although we registered 102 species for each site, Shannon-Wiener diversity index and Pielou's evenness index, respectively, were slightly higher in OES (H' = 3.93; J' = 0.85) than in IGR (H' = 3.87; J' = 0.83). Among birds with various feeding habits, the highest percentage was recorded for understory insectivores in both areas. However, higher percentage of canopy frugivores was found in OES and higher percentage of canopy and understory nectarivores and canopy carnivores was registered in IGR. Moreover, in IGR higher abundance of omnivores was registered than in OES. On the other hand, in OES more specialist species were found while in IGR the percentage of generalist species was higher. Variations in diversity and evenness compared with three previous studies in the same areas showed higher values in the current study. Interestingly, the proportions of understory insectivores were maintained for both areas, however, in IGR higher percentage of omnivores and in OES more specialists than canopy frugivores and understory insectivores, respectively, were reported. Thus, in OES the specificity of feeding habits was maintained, but in IGR the percentage of generalists increased. This might be associated with the response to the edge effect which occurs in IGR's fragment, in particular due to the relation of shape versus size, which would determine its low perimeter.
Keywords: bird community; forest remnants; low-land rainforest; tropical semi-deciduous forest; South-east South America